CREATIVE ECONOMY BRANDING: CONQUERING MARKETS THROUGH INNOVATION AND BRAND EXCELLENCE - Tekat Sukomardojo; Fahrizal Anwar; Dedi Djalipa; Khotimatul Barki; Saida Zainurossalamia ZA (Branding: Jurnal Manajemen dan Bisnis, 2023)
Creative economy plays a vital role in making innovative contributions to the economy amid digital transformation and globalization. The main objective of this research is to identify the relationship between the creative economy, innovation, and branding. This study employs a qualitative approach, utilizing data collection techniques through interviews and document analysis, while also integrating case studies to gain diverse perspectives on the relationship among these three elements. The research findings indicate that branding within the creative economy is a crucial component in building a strong brand identity and driving innovation. Innovation in the branding process enables brands to compete uniquely, attract customers, and retain loyal clientele. The research results also illustrate the distinctions between conventional branding and branding within the context of the creative economy. Conventional branding primarily focuses on the functional benefits of products or services, whereas branding in the creative economy emphasizes the emotional connection between the brand and consumers, as well as the cultural messages or lifestyle conveyed by the brand. In conclusion, this study underscores the crucial role of branding and innovation in the success of the creative economy. Within the context of the creative economy, branding is not merely a tool for brand differentiation but also an expression of the brand's deep-seated vision, values, and uniqueness.